Constant Elasticity of Substitution Production Functions - McFadden, Daniel (Review of Economic Studies, 1963)
Journal Article Constant Elasticity of Substitution Production Functions Get access Daniel McFadden Daniel McFadden Pittsburgh Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 2, June 1963, Pages 73–83, https://doi.org/10.2307/2295804 Published: 01 June 1963